2020
DOI: 10.1021/acscatal.0c04108
|View full text |Cite
|
Sign up to set email alerts
|

A Pioneering Career in Catalysis: Manfred T. Reetz

Abstract: In this invited Account, we highlight the enormous scientific breadth of our mentor Professor Manfred T. Reetz. It stretches from the development of organometallic reagents and transition metal catalysts to the adventurous idea of directed evolution of chemo-, stereo-, and regioselective enzymes, which he considered to be most important. We hope to show that Reetz did not consider these research areas to be totally unrelated realms, and attempt to reveal his transdisciplinary way of thinking about methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…Rather, a self‐critical, tone‐downed vocabulary is called for, in which important results of competitors are cited in a clear manner. But it should wake the interest of the reader! [17–22] I believe that the mentor himself/herself should act similarly, [13,21] which includes the avoidance of exaggerated claims on his/her website. I realize that today the trend goes in the opposite direction.…”
Section: Different Mentoring Systems Existmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, a self‐critical, tone‐downed vocabulary is called for, in which important results of competitors are cited in a clear manner. But it should wake the interest of the reader! [17–22] I believe that the mentor himself/herself should act similarly, [13,21] which includes the avoidance of exaggerated claims on his/her website. I realize that today the trend goes in the opposite direction.…”
Section: Different Mentoring Systems Existmentioning
confidence: 99%
“…Of course, it should attract the attention of potential readers, reviewers and editors. Some suggestions have been made on how to write optimal publications, [18–21] and boring ones! [22] While I do not agree with all of the opinions in some of these works, it may be worthwhile to take a look. An article on publication success in biology [23] may also be of interest to some readers of my essay. If an error in a published paper has been discovered by the authors themselves or by someone else in the group or by a scientist from somewhere else, then it the responsibility of the coworker(s) and the group leader to inform the editor of the respective journal as soon as possible [13] .…”
Section: Different Mentoring Systems Existmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The concept of directed evolution of stereoselective enzymes as catalysts in organic chemistry and biotechnology was proposed as early as 1997, 17 and a plethora of studies in this field has emerged since then. [18][19][20][21][22][23][24] In particular, the engineering of stereospecificity of ADHs has gained much attention because optically active alcohols are essential building blocks in the pharmaceutical industry. Several studies revealed that altering specific protein residue(s) of ADHs is an elegant technique for optimizing their stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The principal immobilization methods reported of fructosyltransferases mainly include adsorption, covalent binding, entrapment, and cross‐linking, and it is considered that adsorption is a simple method with physical interactions (e.g., ionic interactions) 18, 19. There are some protein engineering methods used for enhancing stability, catalytic activity, stereoselectivity, and other characteristics of enzymes, such as error‐prone PCR (epPCR), DNA shuffling, saturation mutagenesis, and iterative saturation mutagenesis (ISM) 20. Protein engineering methods (e.g., mutagenesis via introducing disulfide bridges) have been also employed to improve the substrate utilization rate, catalytic efficiency, and stability of fructosyltransferases 6.…”
Section: Introductionmentioning
confidence: 99%